NEUROLOGICAL CHANGES IN HIV INFECTION - Yakubova Nigina Sadriddinovna; Djuraeva Kamola Stanislavovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Summary: One of the target organs of HIV is the nervous system: only 1/10,000 of the peripheral blood lymphocytes of AIDS patients are infected with the virus, while in brain tissue HIV affects every hundredth cell. Accordingly, one of the common manifestations of HIV/AIDS is damage to the nervous system. Neurological complications of HIV infection can be either caused by the retrovirus itself or due to opportunistic infections, tumors, cerebrovascular pathology, and the toxic effects of antiretroviral drugs. The clinical and epidemiological features of HIV infection, damage to the nervous system in AIDS, the course of opportunistic infections and their specific treatment among the adult population in the Samarkand region are analyzed.